Climate Significance of Land Cover Change in Iraq (Journal of the College of Basic Education, 2022)
This study deals with the magnitude of influence of various geographicalfactors and meteorological variables on land cover among six meteorologicalstations Rabiah, Anna, Kirkuk, Mosul, Baghdad and Najaf. The statistical analysis focuses on the means of annuals during 1961-1995The geographical factors include distance from the Najaf station and the effecttowards studied stations. The meteorological variables considered include windspeed, mean temperature and relative humidity. Regression analyses wereperformed with distance and surface temperatures. Results revealed that surfacetemperature affected land cover across all study. Temperatures in land cover(vegetated areas) were lower than those in other area in seasons. Relativehumidity has significant on all the stations has been studied with land cover asgetting increase as close to be near land cover, the relation stronger in the northand in winter season. Wind speed has no significant only minor influence insummer on the north stations,Rabiah,Anaa, Kirkuk and Mosul because theextension of the mountains from the northwest to the southeast is a responsiblefactor affecting the wind speed since, topographically ,lands are high in the westand east ,and depressed in middle and south. By calculating, adjusting andunified the studied station with same period for one high on sea level for meantemperature, it was found same result of effective of land cover. Introduction